2023
DOI: 10.3390/v15030790
|View full text |Cite
|
Sign up to set email alerts
|

One Health Surveillance Highlights Circulation of Viruses with Zoonotic Potential in Bats, Pigs, and Humans in Viet Nam

Abstract: A One Health cross-sectoral surveillance approach was implemented to screen biological samples from bats, pigs, and humans at high-risk interfaces for zoonotic viral spillover for five viral families with zoonotic potential in Viet Nam. Over 1600 animal and human samples from bat guano harvesting sites, natural bat roosts, and pig farming operations were tested for coronaviruses (CoVs), paramyxoviruses, influenza viruses, filoviruses and flaviviruses using consensus PCR assays. Human samples were also tested u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 71 publications
0
5
0
Order By: Relevance
“…Indeed, a recent study showed that the ACE2 mRNA expression level within bats greatly varies between organs and is higher in the intestine than in the kidney, for example [ 77 ]. Enteric shedding of bat sarbecoviruses therefore constitutes a risk of spillover, especially when considering people frequently exposed to bat guano such as guano collectors, people working in guano farms or people visiting caves who are exposed to guano dust [ 47 , 49 ]. Knowing the ability of Vietnamese Rhinolophus sp.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, a recent study showed that the ACE2 mRNA expression level within bats greatly varies between organs and is higher in the intestine than in the kidney, for example [ 77 ]. Enteric shedding of bat sarbecoviruses therefore constitutes a risk of spillover, especially when considering people frequently exposed to bat guano such as guano collectors, people working in guano farms or people visiting caves who are exposed to guano dust [ 47 , 49 ]. Knowing the ability of Vietnamese Rhinolophus sp.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study conducted in Southern Vietnam, thirty-four Pedacovirus sequences close to Scotophilus bat CoV-512 were identified in Scotophilus kuhlii bats roosting in bat guano farms [ 48 ]. A more recent study, also implemented around bat guano collection sites and pig farming sites, identified progenitors of pig-infecting Pedacovirus in bats roosting at the human–wildlife–domestic animal (i.e., pig) interface [ 49 ]. Several Merbecovirus- , Tegacovirus- and Nobecovirus -related viruses were also identified, but no Sarbecovirus .…”
Section: Introductionmentioning
confidence: 99%
“…Since the COVID-19 crisis, calls for an integrated One Health surveillance as a key to pandemic prevention and preparedness was highlighted and reemphasized by many scientists and experts. A typical example of One Health approach was implemented in Vietnam, illustrating the high risk for CoV spillover from bats to pigs [ 27 ]. Regarding fungal pathogens, a One Health approach pilot study was carried out in Mpumalanga Province, the Republic of South Africa in 2018.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the mutual dependence between humans and animals, wild animal trade or hunting, deforestation, climate change, intensive agriculture or unlimited urbanization increase contacts between humans and animals and thus also the risk of viral emergence. For example, very recently in Vietnam, the possibility of the emergence of novel viruses with zoonotic potential in bats has been described, due to close human–animal contacts [ 100 ]. The spillover surveillance is the key for new viral emergence preparedness, for which it is necessary to conduct risk assessments, to monitor wildlife or farms (pigs, poultry, etc.…”
Section: One Health Concept For Preparedness Applied To Nipah Virusmentioning
confidence: 99%
“…Surveillance of all activities that bring animal reservoirs and humans in contact should be implemented in all at-risk countries for NiV, but in the field, there are multiple organizational, financial, logistical, human, and technical challenges. The successful strategy implemented in Vietnam, based on upstream preparedness in the sanitary surveillance of wildlife, domestic animals, and humans, should serve as an example and favor the identification of the areas with the highest risk of emergence [ 100 ]. In the state of Kerala in India, a team composed of public health experts, microbiologists, and other infectious disease experts coordinate a multidisciplinary response team to verify the diagnosis, control outbreaks, and identify the source of infection.…”
Section: One Health Concept For Preparedness Applied To Nipah Virusmentioning
confidence: 99%